Organic Selenium Resin in Solid Phase Synthesis and Its Application in Constructing Medicinally Relevant Small Organic Molecules - Li, Qing-Si; Wu, Dong-Mei; Zhu, Bing-Chun; Wang, Yu-Guang (Mini Reviews in Medicinal Chemistry, 2013)
Heterocyclic compounds are of high importance in constructing active drug intermediates library. The emergence of solid-phase and combinatorial chemistry has led to renewed interest in using organoselenium resins to library drug-like production. In this mini review, we summarize the construction of heterocyclic compounds libraries such as isoxazoles, oxadiazoles, triazoles, pyrimidines, pyrrolines, indolines, benzopyrans, furans etc. using organoselenium resins. And it provided efficient and practical ways for the preparation of a variety of well-defined functional heterocyclic compounds with the advantages of good yields, high purity, straightforward operations, broad range and high diversity of the products, lack of odor, and good stability of the resins, all of these give expression to green chemistry.
Keywords: combinatorial chemistry